2011
DOI: 10.1039/c1sm05428g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and biological evaluation of self-assembled cubic phases for the polyvalent inhibition of cholera toxin

Abstract: The inverse cubic phase derived from the self-assembly of surfactants in water offers a unique threedimensional platform for protein binding. Colloidally stable, sub-micron dispersions of the inverse bicontinuous cubic phase (cubosomes) impart an unusually large interfacial area for presentation of small molecules to selectively bind proteins of interest. Cubosomes of the phytantriol/water system were prepared and the receptor for cholera toxin (CT), monosialoganglioside G M1 (G M1 ), was integrated within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…113 The encapsulation of proteins within cubosome systems has been investigated by various groups. 96,[114][115][116] The protein may be incorporated via one of two methods. The rst is to add the protein in solution to pre-formed cubosomes.…”
Section: Cubosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…113 The encapsulation of proteins within cubosome systems has been investigated by various groups. 96,[114][115][116] The protein may be incorporated via one of two methods. The rst is to add the protein in solution to pre-formed cubosomes.…”
Section: Cubosomesmentioning
confidence: 99%
“…A recent surface plasmon resonance (SPR) study by Fraser et al found that cholera toxin (CT) 'binds' to phytantriol cubosomes doped with the membrane glycolipid receptor for cholera toxin, monosialoganglioside GM1. 116 The specic nature of the binding was demonstrated by an absence of binding by control proteins (mouse IgG, lysozyme and ricin). 116 Binding of such cubosomes to surfaces suitable for biosensing applications was achieved by subsequent doping with the biotin-functionalized amphiphile 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[biotinyl(polyethyleneglycol)-2000] (bDSPE).…”
Section: Cubosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly the need for better models of the membrane environment for membrane proteins and peptides is seen. Cubic phases are being used for crystallography 34 and such systems 35 could possibly be used for solid-state NMR structural studies of membrane peptides and proteins. Cubic phases give relatively narrow lines due to fast diffusion of lipids around highly curved surfaces and could be used for MAS studies to enhance spectral resolution.…”
Section: Membrane-active Peptides In Model Systemsmentioning
confidence: 99%
“…They allow for the incorporation of multiple components such as targeting ligands, fluorescent molecules and therapeutic agents, offering the potential to act as tissue targeting and multimodal imaging and therapeutic agents. [33][34][35][36][37] Recently, Boyd et al reported the phase transfer of hydrophobic gold nanorods into aqueous dispersion of lipidic mesophase submicron particles. 38 A number of reports have investigated methods of surface functionalising hydrophobic SPIONs with hydrophilic ligands such as polymers and small molecules to make them colloidally stable in water [39][40][41] and occasionally buffer.…”
Section: Introductionmentioning
confidence: 99%